The relationship of physical balance of the ration to energy value and tissue formation in fat lambs. - Cox, R.F.; Mackintosh, D.L.; Smith, E.F.; Hughes, J.S. (Kansas Agricultural Experiment Station, 2012)
Many tests have been completed at this station bearing on some phase of physical balance in sheep rations. Differences in gains consistently have favored a medium proportion of concentrates to roughage over either more concentrated or more bulky rations. It was deemed advisable to determine whether this difference in gains would be expressed in the distribution of fat throughout the carcass.
Keywords: Lamb; Energy value; Tissue; Gain